MERDEKA 74” (MINAPADI BERSAMA DENGAN IKAN LOKAL 7 SPESIES DAN 4 LEGOWO) - Mahendra Mahendra; Zuriat Zuriat; Alaudin Alaudin; Fazril Saputra; Sufal Diansyah; Citra Dina Febrina; Farah Diana; Muhammad Arif Nasution; Zulfadhli Zulfadhli; Fitria Rahmayanti (Universitas Teuku Umar, 2020)
The purpose of this Community Service is to apply the research results of the proposer team's research for community empowerment in Pante Ceureumen District, West Aceh. Research results are applied to the activity program MERDEKA 74